Altered memory‐related functional connectivity of the anterior and posterior hippocampus in older adults at increased genetic risk for Alzheimer's disease. Issue 1 (27th October 2015) - Harrison, Theresa M.; Burggren, Alison C.; Small, Gary W.; Bookheimer, Susan Y.
Abstract: The hippocampal complex is affected early in Alzheimer's disease (AD). Increasingly, altered functional connectivity of the hippocampus is recognized as an important feature of preclinical AD. Carriers of the APOEɛ4 allele are at an increased risk for AD, which could lead to altered hippocampal connectivity even in healthy older adults. To test this hypothesis, we used a paired‐associates memory task to examine differences in task‐dependent functional connectivity of the anterior and posterior hippocampus in nondemented APOEɛ4 carriers ( n = 34, 18F) and noncarriers ( n = 46, 31F). We examined anterior and posterior portions of the hippocampus separately to test the theory that APOEɛ4‐mediated differences would be more pronounced in the anterior region, which is affected earlier in the AD course. This study is the first to use a psychophysiological interaction approach to query the context‐dependent connectivity of subregions of the hippocampus during a memory task in adults at increased genetic risk for AD. During encoding, APOEɛ4 carriers had lower functional connectivity change compared to baseline between the anterior hippocampus and right precuneus, anterior insula and cingulate cortex. During retrieval, bilateral supramarginal gyrus and right precuneus showed lower functional connectivity change with anterior hippocampus in carriers. Also during retrieval, carriers showed lower connectivity change in the posterior hippocampus with auditory cortex. In each case, APOEɛ4 carriers showed strong negative connectivity changes compared to noncarriers where positive connectivity change was measured. These differences may represent prodromal functional changes mediated in part by APOEɛ4 and are consistent with the anterior‐to‐posterior theory of AD progression in the hippocampus. Hum Brain Mapp 37:366–380, 2016 . ©2015 Wiley Periodicals, Inc.